Novel pathways involved in cisplatin resistance identified by a proteomics approach in non‐small‐cell lung cancer cells. Issue 6 (26th October 2018) - Milone, Maria Rita; Lombardi, Rita; Roca, Maria Serena; Bruzzese, Francesca; Addi, Laura; Pucci, Biagio; Budillon, Alfredo
Abstract: Although platinum‐based chemotherapy remains the standard‐of‐care for most patients with advanced non‐small‐cell lung cancer (NSCLC), acquired resistance occurs frequently predicting poor prognosis. To examine the mechanisms underlying platinum resistance, we have generated and characterized by proteomic approach the resistant A549 CDDP‐resistant (CPr‐A549) and their parental A549 cells, identifying 15 proteins differentially expressed (13 upregulated and 2 downregulated in CPr‐A549). In details, we highlighted a coherent network of proteins clustering together and involved in altered protein folding and endoplasmic reticulum stress, correlated with epithelial to mesenchymal transition process and cancer stem cell markers, where vimentin played a hierarchical role, ultimately resulting in increased aggressive features. By using publicly available databases we showed that the modulated proteins could contribute to NSCLC carcinogenesis and correlate with NSCLC patients prognosis and survival probability, suggesting that they can be used as novel potential prognostic/predictive biomarkers or therapeutic targets to overcome platinum‐resistance. Abstract : By a proteomic approach, a coherent network of proteins associated with cisplatin resistance and ultimately resulting in increased aggressive features were defined. These proteins are involved in altered protein folding and ER stress, correlated with EMT process and CSC markers, where vimentin played a hierarchical role. Publicly available databases interrogation suggest that this protein represent novel potential prognostic/predictive biomarkers or therapeutic targets to overcome platinum‐resistance.